SOFT CORALS (OCTOCORALLIA: ALCYONACEA) IN LY SON ISLANDS, THE CENTRAL OF VIETNAM - Bền, Hoàng Xuân; Dautova, Tatyana N. (Vietnam Journal of Marine Science and Technology, 2012)
Ly Son district belongs to Quangngai province including Dao Lon and Dao Be islands. They were located in central of Vietnam far 20 km from mainland. The environment in Ly Son is considered so different that compare with the ecological environment of near shore reefs of Vietnam. The reefs exist in the turbidity but calm waters. Especially, the reefs which located far from the mainland coast are studied less interested than offshore. The total 85 specimens were collected. The results of examination are recorded 60 taxa including 10 genera and 5 families in this area. Among these presents, two genera and 33 species are firstly recorded in comparison with the octocoral fauna of Vietnam which fauna has been the subject of several studies. The result showed that 14 species of Sinularia, 9 species of Lobophytum, 6 species of Sarcophyton genera are newly recorded in Vietnam. Meanwhile, only one new species belonging to the Hicksonella, Paralemnalia, Nephthea, Xenia genera is firstly recorded in Vietnam. Tóm tắt: Lý Sơn là huyện đảo thuộc tỉnh Quảng Ngãi cách đất liền 20 km, bao gồm hai đảo là Đảo Lớn và Đảo Bé. Điều kiện môi trường ở đây được xem là khác biệt so với vùng nước ven bờ nơi mà môi trường nước không trong nhưng khá tĩnh lặng. Mặt khác, những vùng rạn xa bờ như Lý Sơn càng có ít các nghiên cứu về đa dạng sinh học trong hệ sinh thái rạn san hô. Trong số 85 mẫu thu thập đã xác định được 60 taxa thuộc 10 giống và 5 họ san hô mềm. So với các nghiên cứu trước đây ở vùng biển Việt Nam, kết quả phân tích đã xác định được 2 giống và 33 loài mới ghi nhận lần đầu cho vùng biển ven bờ Việt Nam. Trong đó giống Sinularia có số loài mới nhiều nhất là 14 loài, tiếp đến là Lobophytum 9 loài, Sarcophyton 6 loài. Bốn giống còn lại  là Hicksonella, Paralemnalia, Nephthea, Xenia mỗi giống có một loài mới ghi nhận lần đầu tiên cho vùng biển Việt Nam.